Consumer preferences for upcycled ingredients: A case study with biscuits. (September 2020) - Grasso, Simona; Asioli, Daniele
Highlights: First study on UK consumers' preferences for foods with upcycled ingredients. 4 attributes were used: price, type of flour, protein content and Carbon Trust label. On average consumers disliked the sunflower upcycled ingredient in biscuits. 3 consumers' groups identified: price sensitive, traditionalist and environmentalist. Implications for future labelling strategies for policy makers and food producers. Abstract: Nowadays, there is a growing interest to add value to food industry by-products and incorporate them as new ingredients for novel food products. However, there is very little knowledge about consumers' reactions towards novel food products made with upcycled ingredients. This manuscript provides the first critical scientific investigation of UK consumers' preferences for novel food products made with upcycled ingredients using four attributes: price (£0.40/300 g pack or £1.50/300 g pack), flour ("with wheat flour" or "with upcycled sunflower"), protein ("source of protein" or no information) and Carbon Trust label ("with Carbon Trust label" or no label). Using a hypothetical ranking experiment involving biscuits, results showed that consumers prefer biscuits made with conventional (i.e., wheat) flour and tend to reject biscuits made with upcycled sunflower flour. Results suggest there is heterogeneity in consumers' valuation, with three groups identified: the first group with price sensitive consumers and the strongest preferences for low price biscuits, the second group with traditionalist consumers and strongest rejection for upcycled sunflower-flour, the third group with environmentalist consumers and the strongest preference for biscuits with the Carbon Trust label. Most consumers had not heard of upcycled ingredients before, but they would consider buying foods with upcycled ingredients. These findings provide insights into the psychology of consumers' preferences, which can be used to most effectively communicate the benefits of upcycled ingredients to the public. This will also have important implications for future labelling strategies for policy makers providing valuable insights to upcycled food products' manufacturers.